1970
DOI: 10.1139/b70-140
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of ammonia to symptom expression in apple shoots inoculated with Erwinia amylovora

Abstract: Apple stem tissue exposed to ammonia vapors reproduced the symptoms of fireblight. The stem tissue infected with Erwinia amylovora evolved sufficient amounts of ammonia to account for symptom development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1973
1973
1995
1995

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…We are now attempting to locate more definitely the regions, chromosomal or extrachromosomal, which determine plant virulence. Such refinements are expected to provide bases for evaluating the several proposed mechanisms (8,9,11,12) pertaining to the virulence of E. amylovora for plants.…”
Section: Ea178-m173s-v14mentioning
confidence: 99%
See 2 more Smart Citations
“…We are now attempting to locate more definitely the regions, chromosomal or extrachromosomal, which determine plant virulence. Such refinements are expected to provide bases for evaluating the several proposed mechanisms (8,9,11,12) pertaining to the virulence of E. amylovora for plants.…”
Section: Ea178-m173s-v14mentioning
confidence: 99%
“…Erwinia amylovora (Burrill) Winslow et al, the bacterium causing fire blight disease of pears and apples, affects a wide range of plants within the family Rosaceae (6). Although considerable effort has been expended in attempts to clarify the mechanism(s) of plant virulence in this economically significant plant pathogen, there is as yet no certainty about the precise virulence factors associated with the production of disease symptoms (7)(8)(9)(10)(11)(12)14). Initially, Goodman and collaborators (9,11,12) suggested that ammonia produced by E. amylovora might alter adversely the structure of the plant membrane protein and thus behave as a necrotoxin.…”
mentioning
confidence: 99%
See 1 more Smart Citation